2012
DOI: 10.1111/j.1365-3059.2011.02578.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Hymenoscyphus pseudoalbidus on infected ash logs

Abstract: Ash decline induced by Hymenoscyphus pseudoalbidus is an emerging disease that severely affects Fraxinus excelsior stands in Europe. There has been an invasive spread of the disease from east to west in Europe over the last decade. Wood discoloration on infected trunks has been reported, but few data are available on the involvement of H. pseudoalbidus in such symptoms. Transport and trade of ash logs could introduce the pathogen into disease-free areas and therefore accelerate its dissemination. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
134
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(149 citation statements)
references
References 26 publications
14
134
1
Order By: Relevance
“…Collar necroses occurred more frequently in plots with a higher proportion of ash on the total basal area of all tree species, which is related to increased amounts of inoculum. Moreover, the probability for root collar infection was significantly greater for heavily defoliated trees, which is in agreement with other studies that demonstrated a relationship between collar necroses prevalence and crown symptoms [15,16].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Collar necroses occurred more frequently in plots with a higher proportion of ash on the total basal area of all tree species, which is related to increased amounts of inoculum. Moreover, the probability for root collar infection was significantly greater for heavily defoliated trees, which is in agreement with other studies that demonstrated a relationship between collar necroses prevalence and crown symptoms [15,16].…”
Section: Discussionsupporting
confidence: 81%
“…On average, planar terrain is more humid than steep ground, as water takes much more time to drain off. Thus, the higher collar necroses prevalence at more planar sites is in agreement with other studies that indicated increased risks of collar necroses on wet or humid sites or sites that are periodically flooded [15,16,18,19]. Moreover, the prevalence was highest in the Upper Rhine Valley and Lake Konstanz region, where ash usually grows on humid or wet sites.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…While most of the native Fraxinus species are susceptible to the borer, F. quadrangulata is considered resistant (Tanis and McCullough 2012), but this species seemed to be highly susceptible to ash dieback in our study. Regarding potential pathways of introduction of H. fraxineus to North America arrival via airborne ascospores seems less plausible than introduction via import of infected but asymptomatic plants, seeds (Cleary et al 2013a) or wood (Husson et al 2012). Given the higher genetic variation (Cleary et al 2016;Gross et al 2014b) and presumably also higher virulence of East Asian strains (Gross and Sieber 2016), introductions from East Asia would be especially critical (Landolt et al 2016).…”
Section: Future Prospects In Europe and North Americamentioning
confidence: 99%